Quality of life among elderly in community setting: Pondok Pasir Tumboh, Madrasah Diniyah Bakriyah, Kota Bharu,Kelantan - Tinggal, Norfairuziana (Universiti Sains Malaysia, 2009)
Life expectancy seems to increase from year to year and cause the increasing of the older people worldwide. Unfortunately, this does not ensure a good quality of life among older population if their physical, psychological and social needs are not met. A good quality of life among elderly in community setting had been seen to be related with demographical data and environmental condition which might be worsens or improves quality of life. The study is purposely to evaluate the quality of life among elderly in Madrasah Diniyah Bakriyah, Pondok Pasir Tumboh, Kota Bharu, Kelantan. Apart from that, it is conducted to determine the relationship of demographical data and environmental condition with quality of life among elderly in the residency.ln the study, 76 respondents have been chosen using purposive sampling. Data from an interview based on questionnaire which consisted of socio-demographical data and WHOQOL· BREF were collected in 6 weeks and processed by using Statistical Package for Social Science (SPSS) 12.0 descriptively, with the p-value of 0.05 for Chi·square Test. From the study, 47.4% respondents stated that their quality of life is good while 52.6% are moderate. Demographical data which have a significant relationship with quality of life are sex (p=0.046), age (p=0.037) and educational level (p=0.013) while for the environmental condition are recreational facilities (p=0.023), health services (p=0.018) and transportation services (p=0.011). Sex is related to QOL because women, who are less apt to have a spouse to care for them as their age increase, perceived poorer QOL than men. Age also related to QOL because higher age will increase dependency and decrease QOL. Level of education associated with QOL because studying increased self-esteem. Recreational facilities. health services and transportation services seem to be related with quality of life because they can prevent physical and psychological dependency.